Citrullination of Epithelial Neutrophil–Activating Peptide 78/CXCL5 Results in Conversion From a Non–Monocyte‐Recruiting Chemokine to a Monocyte‐Recruiting Chemokine. Issue 10 (October 2014) - Yoshida, Ken; Korchynskyi, Olexandr; Tak, Paul P.; Isozaki, Takeo; Ruth, Jeffrey H.; Campbell, Phillip L.; Baeten, Dominique L.; Gerlag, Danielle M.; Amin, M. Asif; Koch, Alisa E.
<x xml:space="preserve">Abstract</x> Objective To examine whether the citrullinated chemokines epithelial neutrophil–activating peptide 78 (ENA‐78)/CXCL5, macrophage inflammatory protein 1α/CCL3, and monocyte chemotactic protein 1/CCL2 are detected in the biologic fluid of patients with rheumatoid arthritis (RA), and if so, to determine the biologic activities of these chemokines. Methods Recombinant human chemokines were citrullinated by peptidylarginine deiminase. Enzyme‐linked immunosorbent assays were performed to measure the concentrations of citrullinated chemokines in sera from patients with rheumatoid arthritis (RA) and normal individuals and in synovial fluid from patients with RA, patients with osteoarthritis (OA), and patients with other inflammatory rheumatic diseases. The correlation between the citrullinated chemokine levels and clinical data was analyzed. Monocyte and neutrophil chemotaxis assays were performed, and native (noncitrullinated) or citrullinated ENA‐78/CXCL5 was injected into mouse knees to evaluate the biologic activities of these chemokines. Results The concentration of citrullinated ENA‐78/CXCL5 was significantly higher in RA sera and SF than in normal sera and in SF from patients with other rheumatic diseases including OA. In RA SF, a strong correlation between the amount of citrullinated ENA‐78/CXCL5 and the C‐reactive protein level or the erythrocyte sedimentation rate was observed. Citrullinated ENA‐78/CXCL5 induced monocyte chemotaxis via CXCR1 and CXCR2, while noncitrullinated ENA‐78/CXCL5 did not. In a mouse model of inflammatory arthritis, citrullinated ENA‐78/CXCL5 induced more severe inflammation and recruited more monocytes than did noncitrullinated ENA‐78/CXCL5. Conclusion Citrullinated ENA‐78/CXCL5 is highly correlated with RA disease activity and, unlike noncitrullinated ENA‐78/CXCL5, recruits monocytes. These results indicate that citrullinated ENA‐78/CXCL5 may exert previously unrecognized inflammatory properties in RA by recruiting monocytes to inflamed joint tissue.